Equine Gastric Ulcer Syndrome affects fitness parameters in poorly performing Standardbred racehorses - Lo Feudo, Chiara Maria; Stucchi, Luca; Conturba, Bianca; Stancari, Giovanni; Zucca, Enrica; Ferrucci, Francesco (Frontiers in Veterinary Science, 2022)
Equine Gastric Ulcer Syndrome (EGUS) is a highly prevalent disorder in horses, which can be classified, based on the localization of the lesions, as Equine Squamous Gastric Disease (ESGD) or Equine Glandular Gastric Disease (EGGD). Although EGUS is recognized as a common cause of poor performance in racehorses, objective investigations about its relation with athletic capacity are lacking. Therefore, the present retrospective study aims to evaluate the associations between EGUS severity and some fitness parameters measured during an incremental treadmill test in Standardbred racehorses in training. With this aim, data from 87 Standardbred racehorses which underwent a complete diagnostic evaluation for poor performance were reviewed. During gastroscopic examination, a 0-4 score was assigned to ESGD, while EGGD was evaluated for absence/presence; a total EGUS score was obtained by adding 1 point to ESGD score in horses showing concomitant EGGD. Fitness parameters obtained during incremental treadmill test included speed at a heart rate of 200 bpm (V200), speed and heart rate at a blood lactate of 4 mmol/L (VLa4, HRLa4), peak lactate, lactate and heart rate at 30 minutes post-exercise, maximum speed, minimum pH and maximum hematocrit. The associations between fitness parameters and EGUS and ESGD scores were evaluated by Spearman correlation, while Mann-Whitney test was used to compare them between horses with or without EGGD. Statistical significance was set at p<0.05. EGUS grade was inversely correlated with V200 (p=0.0025) and minimum pH (p=0.0469); ESGD grade was inversely correlated with V200 (p=0.0025) and VLa4 (p=0.0363). Although a trend was observed, no significant differences in V200 were observed between horses with or without EGGD (p=0.073); horses with EGGD reached a lower minimum pH (p=0.0087). These results show a negative association between aerobic capacity and EGUS, in particular ESGD. Although different hypotheses have been proposed, including abdominal pain and decreased appetite due to lactate accumulation, the underlying mechanisms are still unknown, and it is not clear whether EGUS represents a cause or a consequence of an early lactate accumulation and post-exercise acidosis.